The impact of legal doctrine on the law-making process in Ukraine - Шевченко, Анатолій Євгенійович; Кармаліта, Марія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Legal doctrine is the basis of convergence within the EU legal system. In addition, it continues to be a major guideline of the fundamental principles of state development and the national legal system of Ukraine formation. Manifestation of legal doctrine in today’s European integration process has got multifaceted character. First of all, it should be noted that the operation of the European legal space is based on universally recognized by civilized nations doctrinal ideas and principles of democracy, inalienability of fundamental rights and freedoms of man and citizen, the rule of law and so on. The law adaptation requires strengthening of the analytical component. This will facilitate maximum use of the research institutions and non-governmental analytical centers. The authorities should cooperate with them for assistance in resolving controversial issues, developing practical recommendations, considering interests and peculiarities of Ukraine, decisions of political importance. The effectiveness of legal integration largely depends on the measures and methods used by countries along the way. It is necessary to stress the importance of legal hermeneutics in the process of the European integration of Ukraine. Conducting large-scale legal reforms, improving the management of public affairs is impossible without the impact of legal doctrine. Development of effective legal policy, justifying of the legal development concept is one of the priorities of the national law. The doctrine finds its expression in various concepts, approaches, theories that are basic for solving issues of law-making; it’s a synthesis of existing information on the legal reality in its all manifestations. That is why it is not restricted only to the knowledge of positive law, analysis of its branches and legal institutions. It contains a vision of law as it should be its imaginary ideal image, justifies the necessity and feasibility of consolidating the rule of law and acts as an important factor of the law formation.